Type and Density of MicroplasticAt The Coast Area Of Manggung Village, Pariaman, West Sumatera Province - Sandrila Putri Elsa; M. Fauzi M. Fauzi; Adriman Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTOne of the plastic wastes that affect the coastal areas in the Manggung Village of Pariaman is microplastic. The presence of microplastics in aquatic and coastal environments can disturb the habitat of macrozoobenthos organisms. The entry of microplastics into animal bodies filter feeders can damage the functioning of organs of the digestive function, reduce growth rates and affect reproduction and is thought to have an impact on the density of macrozoobenthos. This research aims to determine the type and density of microplastics in the coastal area of Manggung Village, Pariaman. This research was conducted in May - June 2019. The sampling point was determined based on the shape of the coast by placing the kuadrat at the lowest, midpoint, and highest tide. The area of the kuadrat used is 50 x 50 cm with a depth of 10 cm of sediment. The results of the research have been found 4 types of microplastic namely fiber, fragment, film, and foam with a total density of 3640 items / m3. Keywords:plastic waste, shore area, filter feeders, fiber.